Dasya patentissima (Ceramiales, Dasyaceae), a new species from the Cabrera Archipelago (Balearic Islands, eastern Spain) - Pena-Martin, Carolina; Crespo, Manuel B.; Gomez, Amelia (Phytotaxa, 2014)
Morphological studies on the genus Dasya (Ceramiales, Rhodophyta) in the western Mediterranean revealed the existence of a collection from the Balearic Islands (eastern Spain) that differed considerably from the known species in the genus. Evidence is provided to regard it as a new species, which here is named Dasya patentissima. Affinities and divergences to other Mediterranean species, namely, D. ocellata and D. hutchinsiae, are discussed and illustrated.